Quantification of brown adipose tissue fatty acid metabolism in lean and obese subjects using 18F-FTHA positron emission tomography - Saari, Teemu (fi=Turun yliopisto|en=University of Turku|, 2018)
Brown adipose tissue (BAT) has the capacity to generate heat in response to cold stimulation. It primarily utilizes its own triglyceride storages but also circulating plasma glucose and free fatty acids. In rodents BAT has an important role in body temperature maintenance. Rodent BAT is also activated postprandially. BAT has also been shown to prefer FFAs to glucose as a source for energy in rodents. The role and significance of BAT in humans is not yet clear. BAT glucose uptake and blood flow are increased in cold conditions. Obesity and age have been associated with blunted BAT activity. There are conflicting reports on human BAT activity after meal digestion. Using PET/CT technique our aim was to quantify BAT fatty acid uptake using 18F-FTHA and perfusion using 15O-H2O during cold exposure, room temperature fasting and room temperature postprandial conditions. We wanted to evaluate and compare different responses of BAT to different stimulus, and compare differences between lean and obese subjects. In this study we showed an increased BAT FAU and blood flow during cold exposure compared to room temperature results. Postprandial influx rate of 18FFTHA was higher in BAT compared to cold exposure in lean subjects. Postprandial BAT blood flow was similar to cold exposure blood flow, indicating activation by meal. We also showed that BAT activity is blunted by obesity and age. Keywords: brown adipose tissue, free fatty acid, positron emission tomography, thermogenesis, cold exposure, meal induced thermogenesis.